2021
DOI: 10.1088/1755-1315/880/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of carbon dioxide and methane from dairy cattle manure

Abstract: There is an increasing interest in reducing production and emissions of greenhouse gases to combat global warming. Greenhouse gases can be produced through animal production operations. One of the major sources of greenhouse gases emitted from the animal farming is dairy cattle barns. This study measured the CH4 and CO2 emissions from dairy cattle manure decomposition trapped inside the static chambers through anaerobic digestion process by bacteria and at regular intervals by focusing on animal age and manure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Other researchers have also found a positive correlation between insect activity on cattle manure and CO 2 emissions [22,66], and between higher soil temperatures and CO 2 emissions during the summer season [9]. laboratory conditions (units were transformed from percentages into g per kg of dry manure considering manure moisture of 85%) [63].…”
Section: Carbon Dioxide Emissionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Other researchers have also found a positive correlation between insect activity on cattle manure and CO 2 emissions [22,66], and between higher soil temperatures and CO 2 emissions during the summer season [9]. laboratory conditions (units were transformed from percentages into g per kg of dry manure considering manure moisture of 85%) [63].…”
Section: Carbon Dioxide Emissionsmentioning
confidence: 98%
“…The cumulative CO 2 emitted during the 16-day sampling period (cumulative CO 2 ) was between 0.1 and 136.5 g CO 2 •kg −1 manure. Hanafiah et al found cumulative CO 2 emissions between 30.5 and 50.9 g CO 2 •kg −1 manure after 8 days of sampling under laboratory conditions (units were transformed from percentages into g per kg of dry manure considering manure moisture of 85%) [63].…”
Section: Carbon Dioxide Emissionsmentioning
confidence: 99%
“…Ayrıca, NH3 ve N2O gibi sera gazı emisyonlarına neden olan bileşiklerin oluşuna neden olmaktadır (Taban ve Turan 2012 ). Doğal gübrelerin yaşam döngüsü incelendiğinde hem metan hem CO2 açığa çıkardıkları bilinmektedir (Hanafiah 2021). Sentetik gübreler ise hem üretimleri sırasında, hem de azotlu gübrelerde bulunan azotun, gübre toprağa atıldıktan sonra havaya karışması sebebiyle sera gazlarına sebep olmaktadır.…”
Section: Gübrenin Karbon Ayak İzine Etkisiunclassified